Evaluationof compact air-induction flat fan nozzles for herbicide applications: Spray drift and biological efficacy - Wang, Shilin; Li, Xinjie; Nuyttens, David; Zhang, Lanting; Liu, Yajia; Li, Xue (Frontiers in Plant Science, 2023)
Nozzles are the most critical component of sprayer for pesticide application. Recently, the air-injector nozzles and twin flat fan air-injector nozzles began to be used for herbicide spraying. In order to highlight the role of air-injector nozzle in herbicide spraying, this paper compares the effects of the air-injector nozzles and standard flat fan nozzle on atomization, deposition, drift and weed control efficacy. Droplet spectrums of nozzles were measured by a laser particle size analyzer, and drift potentials were determined in accordance with the ISO 22401. A field study was conducted to compare the spray drift and the control efficacy between standard flat fan nozzles and air-injector nozzles. The droplets of the standard flat fan nozzles LU and ST were fine or very fine, while those of the air-injector nozzles IDK and IDKT were medium or coarse. Drift potential of nozzles exhibited a good consistency with droplet diameter, which showed that the air-injector nozzles were beneficial to drift reduction. On the whole, there were no significant difference in biological efficacy between standard flat fan nozzles and air-injector nozzles in field application. The control effects of the standard and air-injector flat fan nozzles were all greater than 80% both in the maize and wheat fields. The air-injector nozzles can greatly reduce the spray drift of the droplets, which is of great significance for the protection of the environment and the surrounding sensitive crops. It is recommended to use air-injector nozzles for herbicides application.